REFLECTIONS FROM THE SOCIO-DEMOGRAPHIC ANALYSIS OF ACUTE HEPATITIS B DIAGNOSES, IN BRAZIL, IN THE PERIOD FROM 2007 TO 2018 - Barbosa Martins, Bianca; Carolina Matias Pires, Ana; Luiza Carneiro Carvalho Gonçalves, Maria; Gleiser de Oliveira Moura, Glaedson; Lennon Alves de Lima, John; Letícia Passos Santos, Maria; Neto de Araújo Holanda, Acelino (Health and Society, 2023)
INTRODUCTION: The hepatitis B virus (HBV) is transmitted through corporal fluids as infected people’s blood and semen. Thus, sexual intercourse, blood transfusion, accidents with sharp materials are some of the main mechanisms of transmission of this virus. The HBV has tropism for hepatic cells and the infection by the virus can evolve on variable clinical conditions. The vaccine against hepatitis B has been available on the SUS (Brazilian Unified Health System) since 1998 and is an important collective prevention strategy. The present research aims to perform a sociodemographic evaluation of the hepatitis B diagnoses between the years 2007 and 2018, and to correlate it with the advances of the vaccination coverage in Brazil against hepatitis B. MATERIALS AND METHODS: This is an ecological study, retrospective and descriptive study that it has as methodology the use of secondary data from Sistema de Informação de Agravos de Notificação (SINAM). The sample was composed of all acute hepatitis B’s diagnoses in Brazil during the period from 2007 to 2018, totalizing 21432 records. In the research, the following variables were used: sex, age group, skin color/race, marital status, and schooling. RESULT AND DISCUSSION: This study has demonstrated that the male gender, as well as the brown population represents the largest number of cases. From the evaluation of the variables age and schooling, it was concluded that the population at the age group that, in general, is sexually active (from 20 to 39 years) is the most affected, and the population that presents low schooling characterizes the majority of individuals infected with HBV. FINAL CONSIDERATIONS: It is necessary to expand vaccination coverage by identifying the weak points of vaccination activity, besides the supply of the vaccine, location and adequate schedule to help the health system’s user accession. It is essential that the public policy of information and the campaigns are also directed to health professionals.